(untitled) (Bangladesh Journal of Urology, 2023)
Background and Purpose: Erectile Dysfunction (ED) and Benign Prostate Hyperplasia (BPH) are two health-related problem which are experienced by men aged over forty years. BPH and ED highly affects man’s quality of life . It is necessary to conduct research on the correlations between BPH and ED by using two kinds of valid scores, i.e. the International Prostate Symptoms Scores (IPSS) to determine the severity of BPH and the International Index of Erectile Function-5 (IIEF-5) to detect the existence of ED in BPH patients. Objectives: The aim of this study was to identify ED in symptomatic BPH patients and the correlations between ED and BPH by using IPSS and IIEF-5 score. Materials and Methods: This is a cross-sectional study which analyzes correlations between the severity of BPH and the severity ED by using IPSS and IIEF-5 in the Department of Urology, Bangabandhu Sheikh Mujib Medical University (BSMMU),Dhaka, Bangladesh. Results: Thirty (30) subjects fulfilled the inclusion criteria.80% of the symptomatic BPH patients had ED. The incidence of ED is present in symptomatic BPH patients in the age group of 61-70 years is 100% where in the age group of 50-60 years, the incidence of ED is 60%. The symptom of BPH and ED experienced by these patients are also mostly severe, namely 40% and 50% respectively. The Pearson correlation test also showing that significant and strong correlations do exist between the severities of BPH and ED (r = 0.876, p<0.001). Conclusion: Erectile dysfunction is highly prevalent in the patients with BPH in the range of 80%. The severity of IPSS also correlated with severity of erectile dysfunction. The age group should also be taken into consideration, because increasing age leads to erectile dysfunction. Bangladesh J. Urol. 2023; 26(2): 91-95